Analysis of Government Regulation Number 39 of 2021 and Islamic Law on Slaughter Products at the Mr. Edi Sugara’s Poultry Slaughterhouse - Rahayu Wilujeng, Ninik Sri; Bin Abdul Satar, Abdul Hadi; Zokirova, Gavkhar (Institute of Education and Social Research, 2024)
Slaughter is a way to release the life of an animal using a very easy method, do not hurt, using a sharp knife. One of them is the slaughter of poultry in poultry slaughterhouses that provide poultry (ducks) for the community and are sent to ready-to-eat restaurants. In the villages, many have opened these businesses. However, many poultry slaughterhouse managers do not know the exact slaughter procedures in accordance with Islamic Law and Government Regulation Number 39 of 2021 concerning Halal Product Assurance which will later affect a slaughter result. The purpose of this study is to analyze animal slaughter products at the poultry slaughterhouse of Mr. Edi Sugara in review of Islamic Law and in Government Regulation Number 39 of 2021. The research method used is an empirical juridical approach or called field research. The data collection techniques used were structured interviews, observations, and document studies. The data analysis used in this study used qualitative descriptive. Researchers test and ascertain the validity of the data using triangulation techniques. The results of this research found that animal slaughter products (ducks) at The Poultry Slaughterhouse of Mr. Edi Sugara are in accordance with Islamic Law so that they meet halal slaughter products in Government Regulation Number 39 of 2021.